Dalit Ecologies : Caste and Environment Justice - Sharma, Mukul (Cambridge: Cambridge University Press, 2024)
Dalit Ecologies explores the ecological experiences, histories, and perspectives integrated within Dalit writing, art, and culture. Aligning with theories of environment justice and ecological struggles experienced by Black populations, the book delves into six major themes: caste, earth and earthly environment, labour, and mobility, casteization of technology and industry, climate justice, Dalit Bahujan Anthropocene, and eco-literary tradition. It looks at the relationship between caste and environment, Dalit autobiographies, folktales and novels, city, waste and discard, caste-based industry and occupation, technological injustice, weather, caste and climate change, and Black-Dalit ecologies. Expanding the boundaries of environmental studies, the book brings attention to individuals like Adwaita Mallabarman, Bama, Nek Chand and Deena-Bhadri on the one hand, and specific places and arenas like the rock garden, tannery, brick kiln, steel industry, and sanitation on the other.
Includes Bibliography and index
Keywords: Dalits -- Social conditions -- India; Environmental justice -- India; Caste; Human ecology; Social justice; Environmental policy